PENGUATAN KESEHATAN IBU: IMPLEMENTASI PROGRAM PRARUJUKAN - Leri Septiani; Lina Herlina (Jurnal Widya Laksmi: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aimed to strengthen maternal health through the implementation of the Pre-Referral Flipchart (LBPR) as an effort for early detection and management of high-risk maternal cases in the working area of Ciasem Health Center, Subang Regency. The activity was motivated by the high maternal and infant mortality rate, largely caused by delays in referral and low compliance of health workers in using pre-referral instruments. The program was implemented through training for village midwives, Polindes midwives, and maternal and child health (MCH) coordinators on the use of LBPR, preparation and distribution of guidelines and SOPs, the establishment of internal monitoring teams and champion midwives, as well as regular evaluations. Data were collected through observation, interviews, pre-test and post-test, and analyzed descriptively to assess compliance, knowledge improvement, and skills. The results showed an increase in midwives’ understanding of the function and content of LBPR, improved compliance in using the document during referral processes, and the establishment of a simple monitoring system for monthly evaluation. This program succeeded in improving referral flow, enhancing health workers’ readiness in handling high-risk pregnancies, and encouraging collaboration among health facilities. In conclusion, this educational and systematic intervention proved effective in increasing compliance with LBPR use and has the potential to reduce delays in maternal referrals